DEPENDENCE OF MECHANICAL SPEED OF WELL DRILLING ON THE PORE PRESSURE OF PENETRATED BEDS WITHIN THE PRE-CARPATHIAN FIELD - Chornyi, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper considers the dependence of the mechanical speed of wells drilling on the seams with abnormally high spatial (reservoir) pressures. Forecasting of AHRP is important for improving the degree of completion of layers in process of drilling. As a result of the drilling in of unpredictable areas of AHRP in the Pre-Carpathian region the drill columns often get stuck, one of the reasons for which is not often a justified preventive weighting of the drilling mud. To regulate the pressure in the well during drilling, it is necessary to identify the upper limit of the AHRP zone in time and give it a reasonably quantified characteristics. After analysying the data of wells in the Pre-Carpathian region and those that are being drilled now, it was possible for us to establish that in the case of approaching the well bore to the formation of AHRP, there is an increase in the mechanical speed of drilling in clay rocks, due to the presence of increased inernal pressure and a lower density of these rocks. Increasing of the mechanical speed of drilling under the condition of constant parameters of the drilling regime is also due to heterogeneity of rocks, and stratigraphic transitions from one fold to the other. However, in the case of a double increase of the mechanical speed of drilling in sedimentary layers which are identical in lithology, it is possible to confidently explain this phenomenon by the entrance of the borehole into the AHRP zone. In order to verify the possibility of using mechanical logging to predict the areas of AHRP directly during drilling, we compared the change in the mechanical speed of drilling along the well bore with the data of quantitative and qualitative determination of the areas of AHRP on the results of industrial-geophysical research. Qualitative and quantitative estimation of AHRP zones was carried out, basically, according to the data of electrometry of wells, using the technique of "curves of normally densified clay". For the verification of the findings, direct measurements of the formation pressure with the pressure gauges were used and the data of determination of the formation pressures in the case of transfer of clay solution from the well. Due to the prediction of spatial and reservoir pressures by means of mechanical logging in the process of well laying, we observe a decrease in accidents rate, and an increase in the efficiency of drilling.